Hawaii volcano of 2018 - Berg, Shannon (21st century disasters., 2020)
Describes the causes and effects of the 2018 eruption of the volcano Kilauea in Hawaii. Discusses how to be prepared for volcanic eruptions, and features survivors' stories. Includes a quiz, a timeline, fact boxes, color photographs, a glossary, and further resources.